A systematic review of outcomes associated with withholding or continuing angiotensinconverting enzyme inhibitors (ACE-I) and angiotensin receptor blockers (ARB) prior to noncardiac surgery - Hollmann, Caryl (Department of Anaesthesia and Perioperative Medicine, 2020)
Introduction